Rancang Bangun Aplikasi Pemetaan Layanan Rumah Sakit Darmo Surabaya Dengan Menggunakan Teknologi Layar Sentuh - Setiawan, Yohanes; Sukmaaji, Anjik; Taufik, Vicky M (Jurnal JSIKA, 2012)
Abstract:.Darmo Hospital Surabaya is the one of biggest hospital at Surabaya City. So many visitors visit this hospital every day. Some visitors come to this hospital to visit their families or friends that are treated at this hospital. Some others visitor come to this hospital to do medical check up or visit some hospital service there. Visitors don’t know or don’t remember where is the right room where their families or friends stay, also don’t know or don’t remember where is the hospital service location’s. They must ask that to the security or the information departement there every time they search the different room. This problems need to solved by one application that can give the room location information quickly, self-service and true. Keywords: Application Design, Mapping, Hospital Service.